Systematic review with meta‐analysis: loss of response and requirement of ustekinumab dose escalation in inflammatory bowel diseases. Issue 7 (9th February 2022) - Yang, Hongsheng; Li, Bingyang; Guo, Qin; Tang, Jian; Peng, Bo; Ding, Ni; Li, Miao; Yang, Qingfang; Huang, Zicheng; Diao, Na; Zhu, Xia; Deng, Jun; et al.
Summary: Background: Ustekinumab is effective in treating Crohn's disease (CD) and ulcerative colitis (UC). However, the loss of response (LOR) to ustekinumab and the efficacy of dose escalation have not been systematically explored. Methods: Databases were searched for eligible studies from inception through July 2021. Summary estimates were pooled, and subgroup analyses were performed to explore heterogeneity. Results: We included 14 studies (CD: 13; UC: 1). In CD patients, the annual risk of LOR to ustekinumab and dose escalation among primary responders was 21% (95% confidence interval [CI] 12–31%, 1530 person‐years, n = 9) per person‐year and 25% (95% CI 12–32%, 657 person‐years, n = 5) per person‐year respectively. Clinical response was regained in 58% (95% CI 49–67%, 279 patients, n = 8) of secondary non‐responders after dose escalation (interval reduction or intravenous reinduction). In UC patients, no studies provided data on LOR, but only one study showed that 35% (100/284) of patients underwent dose escalation (or sham dose adjustment), leading to an annual risk of dose escalation of 18% per person‐year. After dose escalation, 58% (14/24) of the patients regained symptomatic remission. Conclusions: Primary responders with CD experienced LOR to ustekinumab at a risk of 21% per person‐year and required dose escalation at a risk of 25% per person‐year. Fifty‐eight per cent of secondary non‐responders with CD may benefit from dose escalation. LOR has not been well characterized in patients with UC. Abstract : In the meta‐analysis, primary responders with Crohn's disease experienced loss of response to ustekinumab at a risk of 21% per person‐year and required dose escalation at a risk of 25% per person‐year. Fifty‐eight percent of secondary non‐responders with Crohn's disease may benefit from dose escalation. However, loss of response to ustekinumab has not been well characterized in patients with ulcerative colitis.